Mecanismos financeiros para a redução de risco associado ao clima: contrato de opções, seguro baseado em índice e fundo financeiro - Sousa, Augusto de Brito (2014)
Water is an essential resource for the social and economic development and to maintaining healthy ecosystems. Due to its economic and social importance is a source of social conflict between the sectors interested in acquiring it and enjoy it, being the lean season far more conflict. So, as a way to harmonize conflicting interests among sectors, this study aimed to investigate and develop financial mechanisms for climate risk management in water resources based on index-based insurance associated option contract and financial background to enable minor variations in resource prices water tended as the principle of compensation to users for transfer when the water supply disruption. The valuation methodology of financial resources that met the sectors was the quantification of economic resources transferred from the equations of specific benefits of sectors. The amounts of transferred water was obtained through the exchange of allocation methodology: linear priorities and assessment system. Five scenarios that divided water availability between two sectors (irrigation and urban) with the following coefficients, respectively, for these sectors (0.10, 0.90), (0.25, 0.75) were simulated, (0, 50, 0.50), (0.75, 0.25) and (0.90, 0.10) for guarantees of 98%, 95% and 90%. Payments of options based on options contracts had lines similar to the negative impacts of irrigation (losses) trends, but with values below these intervals for all warranties and simulated. Losses grew to the scene of coefficients (0.52, 0.48), from which the economic impacts of the urban sector (gains) outweigh the irrigation. However, scenarios for the above coefficients (0.90, 0.10), the gain values decrease below losses. On financial background, only for scenarios with localized coefficients between (0.50, 0.50) and (0.90, 0.10), considered viable scenarios, is that this fund has financial viability, being among the scenarios simulated, the coefficients (0.75, 0.25) having the highest accumulated values. Finally, it is concluded that the economic viability of water transfers only focused on scenarios located between the coefficients (0.50, 0.50) and (0.90, 0.10). Furthermore, it is concluded that the association between options contract based insurance index released flow and financial background can contribute to mutual understanding between the sectors interested in local / regional on the need to harmonize, especially in times water more conflicting in the case, times of water scarcity.